Tuberculous Spondylitis: A Literature Review - Lovely, Anjela Fatma (Jurnal Biologi Tropis, 2025)
Tuberculous (TB) spondylitis, often referred to as Pott's illness, this infectious condition affects the spine and is brought on by Mycobacterium tuberculosis. This literature review aims to increase information and knowledge related to TB spondylitis. The research method used is a type of literature review that discusses the pathophysiology, clinical manifestations, classification, risk factors, diagnosis, management, complications and prognosis of TB spondylitis. Data sources were retrieved through online databases that included literature reviews, research studies, and professional guidebooks over the past ten years related to this topic on library search sites such as Pubmed and Google Scholar. The search results were then reviewed to obtain literature relevant to the study objectives. TB spondylitis occurs in approximately 2% of all TB cases and 15% of all extrapulmonary TB cases, mostly affecting children and people with immunodeficiency due to HIV co-infection. The disease can be classified based on the Gülhane Askeri Tɪp Akademisi (GATA) and the American Spinal Injury Association (ASIA). The approach to the diagnosis of TB spondylitis is not only through history taking, clinical manifestations, and neurological examination, but also includes laboratory examination, radiological examination, and tissue samples examination. The management of TB spondylitis is generally divided into two types that can run simultaneously, namely medicamentosa (main) and surgery (complementary and adjusting the patient's condition). The disease can cause severe neurological symptoms and reduce the patient's quality of life, so early diagnosis and monitoring are necessary to avoid serious complications such as limb paralysis.